О конкуренции этнонимов белорус – беларус в коммуникативном пространстве Беларуси - Tatiana Volynets (Polilog: Studia Neofilologiczne, 2022)
The article examines the features of the use of the ethnonyms belorus – belarus (as well as the words belarusian, belarusan, in belarusian with the last lexeme...) in Russian language media texts presented in the communicative space of Belarus, and assesses the legality /illegality of this process. It is suggested that the appearance and active use in Russian language texts of Belarusian authors (both journalists and Internet users) of lexemes associated (directly and indirectly) with the offi cial name of the country (Belarus) is primarily due to the growth of the national consciousness of the Belarusian people. Despite this, these lexemes cannot be considered as the result of ethnic nationalism, they have every right to exist in the lexical and word-formation system of the Russian language functioning in Belarus. Their appearance is quite predictable and can be interpreted as a consequence of natural language processes, since the functional and semantic nature of motivational relations Belarus – belarus, belarus – belaruska, belarus – belarusan, etc. is quite natural from the point of view of the system of synchronous word formation.